HEPWM using differential evolution technique for three phase voltage source inverter - Azziddin, Mohamad Razali; Kamisman, Norazelina; Mat Lazi, Jurifa; Bahari, Norhazilina (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper presents the implementation of Differential Evolution (DE) algorithm to solve Harmonic Elimination Pulse-Width Modulation (HEPWM) problem. HEPWM is widely used in eliminating the low frequency harmonic of output voltage of the inverter. The DE is a simple and efficient evolutionary algorithm in solving the HEPWM transcendental equation. Operations of DE technique were elaborated and the best approach of mutation strategy has been analyzed. Switching angles of HEPWM were calculated offline using DE technique. Then, the switching angles were applied to three-phase voltage source inverter (VSI). Simulation of DE technique and VSI experiment set up were run in Matlab/Simulink.